Investigation of the finishing characteristics in an internal tube finishing process by magnetic abrasive finishing combined with electrolysis - Muhamad, M.R.; Zou, Y.; Sugiyama, H. (Maney Publishing, 2016)
In this research, the finishing characteristics in a tube's internal finishing process using the method of magnetic abrasive finishing (MAF) combined with electrolysis has been studied. Electrolysis produces an aluminium oxide film that accelerates the removal of the initial hairline morphology on the surface. Subsequently, the film is removed with MAF. This process significantly minimises the surface roughness in a reduced time. The way the finishing conditions, such as the polepipe gap, iron particle size and abrasiveness combinations, and processing time affected the surface morphology in the MAF machining process has been particularly examined. The surface roughness was measured and images of the finished surfaces were recorded to study the morphology changes. Prolonged electrolysis finishing was seen to deepen the oxidation film and pits, which adversely affects the surface. This evidence suggests that the pit residuals contribute to higher surface roughness values.